Use the profit model to evaluate the tax framework Applied Study in the General Authority for Taxation / Iraq - Hussein Khudhair, Ali; Hussain Dawood, Iman; Ali Yousif, Hayder Mohammed (Opción, 2019)
This study deals with the use of the profit model in the assessment of the tax framework with a theoretical framework and then an applied analysis by selecting a sample of the listed companies listed in the Iraqi Stock Exchange. The study period lasted from 2008-2012. The objective of the research is to calculate the cost of financing the property using the capital asset pricing model (CAPM), Capital Assets Pricing Model, and the relationship between return and market risk meas- ured by beta by applying the study to two industrial companies, shedding light on the profit model in industrial companies, analyzing the alternative market portfolio from the companies’ Manal Conclusions of them, the company is characterized by defensive Balsafh because fluctuations in revenue below market fluctuations and also Mkhatrtha less than market risk. The research reached several recommen- dations, including the need to work by companies to improve the growth rate of profits by holding a certain percentage of profits, which improve the real value of shares for these companies.